Increasing Critical Thinking Ability of Students Through Guided Inquiry Model in Learning Photosynthetic Materials in SMA PGRI Pekanbaru: Increasing Critical Thinking Ability of Students Through Guided Inquiry Model in Learning Photosynthetic Materials in SMA PGRI Pekanbaru - Masni, Syarty Eka; Firdaus LN, Firdaus LN; Wulandari, Sri (Journal of Educational Sciences, 2020)
The educational challenges of the 21st century require skills especially in Creativity and Innovation, Critical Thinking and Problem Solving, Communication and Collaboration. The purpose of this research is to show the improving of students’ critical thinking ability of class XII High School PGRI on Photosynthetic material by using a model of Guided Inquiry. The type of this research is quasi experiment using two classes. Experiment class used model learning Guided Inquiry model and control class used conventional model. The design of research used pretest-posttest control group design. The techniques of collection the data was by using cognitive ability tests of critical thinking in pretest and posttest. From the 5 aspects on critical thinking skills: (1) elementary clarification has increased with N the gain; 0.49 (category medium), (2) basic support has increased with N gain 0.66 (moderate category ); (3) inferring has increased with N gain 0.58 (moderate category); (4) advanced clarification has N gain 0.39 (moderate category); (5) strategies and tactic are experiencing increased by 0.05 gain N (low category). Generally, it can be concluded that the skill of students’ critical thinking in SMA PGRI has increased through photosynthesis learning with the Guided Inquiry model